2021
DOI: 10.1177/0025802421992913
|View full text |Cite
|
Sign up to set email alerts
|

Informing reform: The views of legal professionals on the unique aspects of Scottish Law

Abstract: The unique Scottish legal system stands apart from the better-known Anglo-American legal system, with variations relating to jury size (15 vs. 12), the number of verdicts available (3 vs. 2) and majority size (simple majority vs. unanimous). At present, only a handful of investigations have explored the effects of the Scottish ‘not proven’ verdict on jurors, and only a single study has explored the combined impact of the unique elements of the Scottish legal system on juror and jury decision making. The curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Legal scholars commonly cite jury deliberations as an important factor that helps to attenuate the effects of bias in the criminal justice system. 34 , 56 The logic behind this argument is that by randomly selecting a group (usually 12; but 15 in Scotland 57 ) of jurors from the general public, a number of jurors with various biases and beliefs will be selected and that these biases will cancel each other out. 11 , 44 It has also been suggested that deliberations allow jurors to focus more on the “facts” of the case rather than on assumptions and will allow more extreme positions to be scrutinised by the collective.…”
Section: During Evidence Presentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Legal scholars commonly cite jury deliberations as an important factor that helps to attenuate the effects of bias in the criminal justice system. 34 , 56 The logic behind this argument is that by randomly selecting a group (usually 12; but 15 in Scotland 57 ) of jurors from the general public, a number of jurors with various biases and beliefs will be selected and that these biases will cancel each other out. 11 , 44 It has also been suggested that deliberations allow jurors to focus more on the “facts” of the case rather than on assumptions and will allow more extreme positions to be scrutinised by the collective.…”
Section: During Evidence Presentationmentioning
confidence: 99%
“…Despite these findings, a substantial minority of legal professionals indicate a preference for panels of judges to replace juries. 57 …”
Section: During Evidence Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Scotland, unlike other nations that use juries in criminal courts, has three verdicts available to juries (Curley, Munro, et al., 2021). These verdicts are ‘guilty’, ‘not guilty’ and ‘not proven’ (Curley, Munro, et al., 2021).…”
mentioning
confidence: 99%
“…Scotland, unlike other nations that use juries in criminal courts, has three verdicts available to juries (Curley, Munro, et al., 2021). These verdicts are ‘guilty’, ‘not guilty’ and ‘not proven’ (Curley, Munro, et al., 2021). The not proven verdict is an acquittal verdict with the exact same legal implications as a not guilty verdict (Curley, Murray, et al., 2021).…”
mentioning
confidence: 99%